To solve the inequality, we need to determine the values of x that make the inequality true.
First, let's simplify the inequality:
-10(-2x + 3) ≤ 0
We can simplify further by distributing the -10:
20x - 30 ≤ 0
Next, let's isolate the variable x by adding 30 to both sides of the inequality:
20x ≤ 30
Finally, divide both sides of the inequality by 20 to solve for x:
x ≤ 30/20
Simplifying further, we have:
x ≤ 3/2
So, the solution to the inequality is x ≤ 3/2.
Solve the following equality
-10(-2x + 3) _<_
1 answer